PENGEMBANGAN MEDIA PEMBELAJARAN JUMATHJI TERINTEGRASI TGT DALAM RANGKA PENINGKATAN KETERAMPILAN NUMERASI MURID KELAS 3 SD - Mawardi Mawardi; Lunaria Nastiti (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2026)
This research aimed to develop a board game-based learning media called JUMATHJI for multiplication material in third-grade elementary school and to examine its feasibility and effectiveness in supporting students’ numeracy skills. A Research and Development (R&D) approach was employed using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The subjects were third-grade students from elementary schools in Kanigoro sub-district cluster. Data were collected through validation questionnaires, student response questionnaires, and a numeracy test. The data were analyzed using descriptive quantitative techniques to determine the feasibility and practicality of the media, as well as inferential analysis using the Wilcoxon test to examine its effectiveness. The results of the study indicate that the JUMATHJI learning media achieved a very good category based on expert validation and received positive responses from students. The Wilcoxon test showed a significance value of less than 0.05, indicating that students’ numeracy test results had met the minimum mastery criteria (KKM). Therefore, the JUMATHJI learning media is considered appropriate for use in learning to support students’ numeracy skills. The practical implication is that the JUMATHJI media can be used as a learning medium in elementary schools.